Sequential introduction of a multistep testing algorithm and nucleic acid amplification testing leading to an increase in Clostridioides difficile detection and a trend toward increased strain diversity. (24th October 2020) - Skinner, Andrew M.; Yu, Brian; Cheknis, Adam; Pacheco, Susan M.; Gerding, Dale N.; Johnson, Stuart
Abstract: Background: Most clinical microbiology laboratories have replaced toxin immunoassay (EIA) alone with multistep testing (MST) protocols or nucleic acid amplification testing (NAAT) alone for the detection of C. difficile . Objective: Study the effect of changing testing strategies on C. difficile detection and strain diversity. Design: Retrospective study. Setting: A Veterans' Affairs hospital. Methods: Initially, toxin EIA testing was replaced by an MST approach utilizing a glutamate dehydrogenase (GDH) and toxin EIA followed by tcdB NAAT for discordant results. After 18 months, MST was replaced by a NAAT-only strategy. Available patient stool specimens were cultured for C. difficile. Restriction endonuclease analysis (REA) strain typing and quantitative in vitro toxin testing were performed on recovered isolates. Results: Before MST (toxin EIA), 79 of 708 specimens (11%) were positive, and after MST (MST-A), 121 of 517 specimens (23%) were positive ( P < .0001). Prior to NAAT-only testing (MST-B), 80 of the 490 specimens (16%) were positive by MST, and after NAAT-only testing was implemented, 67 of the 368 specimens (18%) were positive ( P = nonsignificant). After replacing toxin EIA testing, REA strain group diversity increased (8, 13, 13, and 10 REA groups in the toxin EIA, MST-A, MST-B, and NAAT-only periods, respectively) and in vitro toxin concentration decreased. The average log10 toxin concentration of the isolates were 2.08, 1.88, 1.20 and 1.55 ng/mL for the same periods, respectively. Conclusions: MST and NAAT had similar detection rates for C. difficile. Compared to toxin testing alone, they detected increased diversity of C. difficile strains, many of which were low toxin producing.